1990
DOI: 10.1073/pnas.87.21.8306
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for involvement of multiple forms of cytochrome P-450 in aflatoxin B1 metabolism in human liver.

Abstract: Liver cancer is a major cause of premature death in many areas of Africa and Asia and its incidence is strongly correlated with exposure to aflatoxin B1 (AFB1).Because AFB1 requires metabolic activation to achieve a biological response, there is a need for detailed knowledge of the mechanism of activation to assess individual risk. We have carried out an extensive study using a total of 19 human liver samples to determine the individual variability in the metabolism of the toxin to mutagenic or detoxification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
9

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 30 publications
4
76
1
9
Order By: Relevance
“…However, these workers implemented different job functions. Another explanation for the different adduct levels with the same exposure could be an interindividual difference in the metabolism of aflatoxin B I to biologically active metabolites or detoxified products (19). One of the workers in the silo at factory B had a fairly high level of aflatoxin B I adducts to albumin although his estimated exposure to dust particles was low, less than 25 070 of the workhours.…”
Section: Discussionmentioning
confidence: 99%
“…However, these workers implemented different job functions. Another explanation for the different adduct levels with the same exposure could be an interindividual difference in the metabolism of aflatoxin B I to biologically active metabolites or detoxified products (19). One of the workers in the silo at factory B had a fairly high level of aflatoxin B I adducts to albumin although his estimated exposure to dust particles was low, less than 25 070 of the workhours.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the cytochrome P450 (CYP) enzyme family, CYP1A2, CYP3A4 and CYP2A6 have been shown to be responsible for the metabolism of the absorbed aflatoxins 7,8 ( Fig. 1).…”
Section: Guanine; Hepatitis B Virusmentioning
confidence: 99%
“…Absorbed AFB 1 and its metabolites are excreted in urine, while elimination to feces is a route for both the unabsorbed AFB 1 and biliary excretion of metabolites formed from the absorbed toxin. Animal studies have shown that under normal conditions 50% of the orally administered dose of AFB 1 is quickly absorbed from the duodenal region of the small intestine 4 and enters the liver through the hepatic portal blood supply.5 AFB 1 is concentrated in the liver and to a lesser extent in kidney, 6 and it is also found in the mesenteric venous blood as free AFB 1 or its water-soluble metabolites.Members of the cytochrome P450 (CYP) enzyme family, CYP1A2, CYP3A4 and CYP2A6 have been shown to be responsible for the metabolism of the absorbed aflatoxins 7,8 (Fig. 1).…”
mentioning
confidence: 99%
“…Assays GS-AFB1 (products of exo and endo epoxides) and AFB,-8,9-dihydrodiol were separated by high-performance liquid chromatography (HPLC) and quantified (A360) as described elsewhere (25,31). Genotoxicity assays involved measurement of the umu (SOS) response in Salmonella typhimurium TA1535 harboring the plasmid pSK1001 using general procedures described elsewhere (32 (9,31,(34)(35)(36)(37) (Table 2). P450 1A2 and some other human P450s can also contribute, but they play a lesser role, even at relatively low AFB, concentrations (31,35,36,38,39).…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxicity assays involved measurement of the umu (SOS) response in Salmonella typhimurium TA1535 harboring the plasmid pSK1001 using general procedures described elsewhere (32 (9,31,(34)(35)(36)(37) (Table 2). P450 1A2 and some other human P450s can also contribute, but they play a lesser role, even at relatively low AFB, concentrations (31,35,36,38,39). P450 3A4 forms only the genotoxic AFBI-8,9-exo-epoxide; P450 1A2 forms both the exo and the nongenotoxic endo isomers (Figure 1)(31).…”
Section: Introductionmentioning
confidence: 99%